Identification and Subtyping of Avian Influenza Viruses by Reverse Transcription Polymerase Chain Reaction (RT-PCR) and Agarose Gel Electrophoresis - Shankar, B.P.; Gowda, R. N. Sreenivas; Pattnaik, B.; Prabhu, B. H. Manjunatha; Sreenivas, B.K.; Vinuthan, M.K.; Ranjith, D.; Pradhan, H.K. (International Journal of Poultry Science, 2009)
Avian Influenza (AI) is caused by type A influenza virus belonging to the family orthomyxoviridae, which is classified into 16 HA and 9 NA subtypes based on two surface glycoprotein’s haemagglutinin (HA) and neuraminidase (NA). In the present study we did identification and HA-subtyping of avian influenza virus by reverse transcription-PCR (RT-PCR) during the first outbreaks of AI in India during 2006. The avian influenza virus is identified by RT-PCR using a set of primers specific to the nucleoprotein (NP) gene of avian influenza virus. The HA-subtypes of avian influenza virus were determined by running with HA subtype specific primers for H5, H7 and H9 RT-PCR reactions, each using a set of primers specific to one HA-subtype. A total of 10,236 tissue / cloacal swab samples, received at the HSADL from various parts of the country, were processed for isolation of AI virus in embryonated chicken eggs. Out of these, 9 samples originating from poultry in Maharashtra (Navapur and Jalgaon) and Gujarat (Surat) states of India were found positive for H5 virus by RT-PCR. All samples received from outbreaks areas were tested by using all tree subtype specific primers(H5, H7 and H9) only H5 RT-PCR reactions was give the product of expected size, and thus the HA-subtype of the virus is determined. One sample gave the positive result with H9 subtype specific primers. The RT-PCR procedure is rapid and sensitive, and could be used for the identification and HA-subtyping of avian influenza virus in organ homogenates.